Mobility as a response to environmental hazards in the urban context: A new perspective on mobility and inequality. (April 2022) - Xia, Chang; Yeh, Anthony G.O.
Highlights: Conceptualization of mobility as a response (MaaR) to urban environmental hazards. Highlight of averting behaviour as the research perspective of mobility under adverse events. A new interdisciplinary dialogue for urban planning, transportation, and environmental health research. Review of recent studies on environmental hazards, (im)mobility, and inequality. Discussion of research gaps and methodological challenges of MaaR. Abstract: In view of the increasing occurrence of urban environmental hazards which can threaten our quality of life and health outcomes, how citizens react to adverse environmental impacts is of great concern. Mobility, as an important part of urban everyday life, is a key concept in understanding individuals' experience in cities and the society; however, this notion has long been understudied with regard to avoiding the harmful effects of environmental hazards. By highlighting the research perspective of averting behavior, we conceptualize mobility as a response (MaaR) to environmental hazards to inform a new interdisciplinary dialogue for transportation, urban planning, and environmental health research. We review a variety of literature in environmental hazards, (im)mobility, and inequality and reveal the challenges posed by MaaR. MaaR would provide empirical evidence on whether, how, and to what extent the effects and social costs of environmental hazards are underestimated and existing environmental inequality are exacerbated. This article puts forward that MaaR is a promising analytical framework through which we can enrich our knowledge on the person-environment relationships.